Near shore oceanographic conditions off SW Portugal in summer 2006 and 2007 from satellite and in situ data - Oliveira, P. B. (2012)
Data from two successive summers are used to characterize the near shore oceanographic conditions south of cape Sines in the SW Portuguese coast. The observed time evolution of the satellite-derived sea surface temperature (SST) and chlorophyll ([Chl]) patterns show that the near shore patterns are very sensitive to the intensity and temporal structure of the upwelling favourable winds. Stronger and more variable winds in 2007 favoured the occurrence of more events of low SST and high [Chl] concentrations in the study area. The full resolution MERIS data revealed the presence of small-scale flow structures in the lee of the cape resulting from the interaction of the coastal jet and coastal morphology. The high spatial resolution of the MERIS instrument allowed the identification of a shadow area south of cape Sines where [Chl] values are usually higher than offshore and north of the cape. The comparison between the MERIS (algal_1 and algal_2) and MODIS [Chl] estimates showed that, despite the similar spatial patterns, MODIS estimates are typically higher in the near shore region. In some images, abnormally high MODIS [Chl] values (> 30 mg/m3) close to the coast lead to spatially averaged [Chl] estimates in the near shore region that are more than double of the MERIS estimates.